Mirroring realities a reflection of the pursuit of liberation in directing Makinal, Eljay Castro Deldoc's Filipino adaptation of Sophie Treadwell's Machinal - Hooshmand, Mary Donna Nour M.
This study discusses my creative process as the director in staging UP Dulaang Laboratoryo's Makinal, Eljay's Castro Deldoc's Filipino Adaptation of Machinal by Sophie Treadwell through the use of Katie Mitchell's The Director's Craft: A Handbook (2008) in structuring the performance and handling reherasals; Anne Bogart's A Director Prepares: Seven Essays on Theatre and the Arts (2001) as inspirational fuel and guide in the challenges faced in directing ; Elinor Fuchs' Visit To a Small Planet: Some Questions to Ask a Play (2004) in creaing the world of the play. Through the process of directing makinal, I was able to explore my capabilities as a director and as an artist. I learned how to weave the fragmented text of the play and to utilize all the elements of the production in telling the narrative of the material. Video design is heavily used to thread the transitions and propel the story of the Young Woman's life in the play. Up Dulaang Laboratoryo's production of Makinal was staged at the Teatro Hermogenes Ylagan and had five performances from April 12(7:00PM), 13 (3:00PM & 7:00PM), to April 14 (3:00PM & 7:00PM) in the year 2019. This study aims that through the experiences and lessons learned through staging Makinal (2019) that this study can serve as a valuable guide for future student directors who aspire to create their own worlds and tell meaningful stories about life.